Case report: Presentations and cytokine profiles of inflammatory non-pulmonary COVID-19 and related diseases in children - Yen-Chun Chao; Yen-Chun Chao; Yen-Chun Chao; Horng-Woei Yang; Lung Chang; Lung Chang; Lung Chang; Lung Chang; Chih-Wen Tseng; Li-Ching Fang; Li-Ching Fang; Li-Ching Fang; et al. (Frontiers Media S.A., 2023)
The coronavirus disease 2019 (COVID-19) pandemic has evolved to dynamic waves of different SARS-CoV-2 variants. Initially, children diagnosed with COVID-19 presented pulmonary involvement characterized by mild diseases. In the later waves of the COVID-19 pandemic, life-threatening non-pulmonary inflammatory diseases such as (1) aseptic meningoencephalitis (ME), (2) acute necrotizing encephalopathies (ANE), and (3) multisystem inflammatory syndrome in children (MIS-C) have been reported, affecting the pediatric population. To alert timely identification and prevention of the life-threatening non-pulmonary COVID-19, we present the cases of ME, ANE, and MIS-C in terms of clinical manifestation, cytokine profile, and follow-up consequences. Based on the immunopathogenesis and risk factors associated with non-pulmonary COVID-19, we delineate strategies for an early diagnosis and treatment to reduce morbidity and mortality in children.